Exploring a risk based approach to solvency management in the Zimbabwean short term insurance industry - Mukonzo, Placxedes (Midlands State University, 2017)
The study sought to explore the adoption of a risk based approach to solvency management in the Zimbabwean short term insurance industry. The review of literature was carried out in order to establish what other authors had to say on the subject. To come up with a sample of 17 short term insurers and reinsurers out of a target population of 33 operational insurance and reinsurance companies, the researcher used stratified sampling technique since the study population comprised of different characteristics. The researcher used questionnaires and structured interviews to collect information. Tables, bar graphs and pie charts were used to present responses from the survey. The results indicated that the insurers and reinsurers are facing challenges in meeting the minimum capital requirement and appreciates the benefits of adopting solvency II. However, the challenges and costs associated with the adoption of solvency II makes its adoption in the Zimbabwean short term industry difficult. The study recommends the modification of the current solvency management system so as to encourage insurers and reinsurers to hold risk based capital and the protect policyholders through reporting rules and the establishment of a policyholder protection fund. It also recommends short term insurers and reinsurers to use effective capital management and risk management systems.